DESIGN AND TEST THE PERFORMANCE OF THE WATER HEATER BY UTILIZING THE EXHAUST HEAT OF THE LABORATORY SCALE AIR CONDITIONER - Gunarto, Gunarto; Eko Julianto; Muhammad Iwan (Jurnal Rekayasa Mesin, 2024)
The purpose of this research is to design and test the performance of a water heater unit that works based on the exhaust heat of the ½ PK Split Air Conditioner condenser which will be used as a power source to heat water with a capacity of 60 litres based on standard hot water temperature. for bathing at 40-45 oC according to the type of use SNI 03-7605-2005 concerning procedures for planning plumbing systems. It is hoped that this research can serve as a guideline for designing a water heater derived from an exhaust heat condenser using a Helical-Coil type heat exchanger. This research uses descriptive research with a quantitative approach. Descriptive research in this study is intended to obtain an overview and information regarding the utilization of an exhaust heat condenser with the addition of a water helical coil heat exchanger and the working process of an air conditioner water heater that utilizes condenser waste heat to produce hot water that can be used for bathing needs. From the test results, the water heater can work well as evidenced by an increase in water temperature reaching 44.40 C in 70 minutes. The energy value in the form of heat that can be utilized by adding a water heater is 1.14785 kJ/second, with a water heater efficiency of 76.23%. Thus the utilization of the air conditioner condenser wastes heat energy and is quite effective for heating water. To be able to save water use for household, business, industrial and other needs that use Air conditioners as air conditioning.